Services for homeless people in Germany during the COVID-19-pandemic a descriptive study - Gräske, Johannes; Koppe, Louise; Neumann, Fränze; Forbrig, Theresa A. (Alice Salomon Hochschule Berlin, 2021)
Design: Across-sectional study was conducted inDecember 2020/January 2021 in the five significant cities of Germany. Sample: 135 of 244 identified service institutions took part in the evaluation. Measurements: This evaluation included changes in institutions’ operating hours as well as capacity for homeless people. Service institutions described changes in guests’ characteristics, moods, and mental burden. Finally, equipment including face masks, coveralls, and gloves was investigated. In addition, the study examined how the cooperation with the health authorities works. Results: Institutions reduced their operating hours and capacity for guests (62.4%). Increased costs, which they had to cover themselves, were reported by 70.9% of institutions. Institutions reported, that guests showed more symptoms of aggression (15%), anxiety (25%), and desperation (32%) and fewer signs of being relaxed (75%). The institutions reported room for improvement in PPE supplies and collaboration with health authorities. Conclusions: Services are limited for a vulnerable population, which shows changes in moods and mental health. Health authorities are not sufficiently engaged to take over the role of institutions in caring for homeless people. In the future, in-depth investigation to improve this is necessary. Quelle: aliceOpen.